PENENTUAN KOMODITAS UNGGULAN PERTANIAN KABUPATEN OGAN KOMERING ULU TIMUR - Putri Ayu Ogari; Irham Irham; Slamet Hartono (Agro Ekonomi, 2014)
The objectives of this study are (!) to know the leading subsector in agricultural sector (2) to identify potential commodities in each agricultural subsectors in East Ogan Komering Ulu District (3) to determine pattern of subsectors and leading commodities of agricultural sector in Ogan Ulu Timur District. Time series date are used in this study namely PDRB data based on current price (2007-2011) and agricultura; commodities harvested area during range time  years (2008-2012)The result of analysis that food-stuff crop subsector and of plantation crop subsector represent is leading agricultural subsector in PKU Timur District. Leading agricultural commodities are cucumber, spinach, swamp, cabbage, banana, chayote, chili dan paddy. Leading plasntations crops are pepper, cocoa, kapok, rubber, and coconuts hybrid.Growth patterns of leading subsectors and commodity in agricultural sectors in Ogan Komering Ulu Timur District consist of Plantation and and forestry subsector as grow  fast subsector. While crops subsector foodcrops subsector includes advanced but depressed, while Animal Husbandry and Fisheries includes subsector lagging behid. Some of leading commodities such as foodscrops subsector consisting of corn, spinach, banana and sapodilla os a commodity advance and grow fast; while rice, sweet potatos eggplant, cucumber, squash, duku, mango, jackfruit, rambutan and barking is a grow fast commodity; whereas peanuts, soybeans, kale, durian, and mangosteen is advance but depressed commodity; cassava, green beans, string beans, chili is great, cayenne, pepper, tomato, avocado and starfruit are commodities lagging behind. The leading commodities crops such as rubber and pepper plantations are advanced and grow fast commodity ; while coconut, cocoa, cotton and sgar included grow fast commodity; while palm oil is a commodity advance but depressed; for coffee and hazelnut included commodities lagging behind.